Association of disrupted circadian rhythmicity with mood disorders, subjective wellbeing, and cognitive function: a cross-sectional study of 91 105 participants from the UK Biobank. (June 2018) - Lyall, Laura M; Wyse, Cathy A; Graham, Nicholas; Ferguson, Amy; Lyall, Donald M; Cullen, Breda; Celis Morales, Carlos A; Biello, Stephany M; Mackay, Daniel; Ward, Joey; Strawbridge, Rona J; Gill, Jason M R; et al.
Summary: Background: Disruption of sleep and circadian rhythmicity is a core feature of mood disorders and might be associated with increased susceptibility to such disorders. Previous studies in this area have used subjective reports of activity and sleep patterns, but the availability of accelerometer-based data from UK Biobank participants permits the derivation and analysis of new, objectively ascertained circadian rhythmicity parameters. We examined associations between objectively assessed circadian rhythmicity and mental health and wellbeing phenotypes, including lifetime history of mood disorder. Methods: UK residents aged 37–73 years were recruited into the UK Biobank general population cohort from 2006 to 2010. We used data from a subset of participants whose activity levels were recorded by wearing a wrist-worn accelerometer for 7 days. From these data, we derived a circadian relative amplitude variable, which is a measure of the extent to which circadian rhythmicity of rest–activity cycles is disrupted. In the same sample, we examined cross-sectional associations between low relative amplitude and mood disorder, wellbeing, and cognitive variables using a series of regression models. Our final model adjusted for age and season at the time that accelerometry started, sex, ethnic origin, Townsend deprivation score, smoking status, alcohol intake, educational attainment, overall mean acceleration recorded by accelerometry, body-mass index, and a binary measure of childhood trauma. Findings: We included 91 105 participants with accelerometery data collected between 2013 and 2015 in our analyses. A one-quintile reduction in relative amplitude was associated with increased risk of lifetime major depressive disorder (odds ratio [OR] 1·06, 95% CI 1·04–1·08) and lifetime bipolar disorder (1·11, 1·03–1·20), as well as with greater mood instability (1·02, 1·01–1·04), higher neuroticism scores (incident rate ratio 1·01, 1·01–1·02), more subjective loneliness (OR 1·09, 1·07–1·11), lower happiness (0·91, 0·90–0·93), lower health satisfaction (0·90, 0·89–0·91), and slower reaction times (linear regression coefficient 1·75, 1·05–2·45). These associations were independent of demographic, lifestyle, education, and overall activity confounders. Interpretation: Circadian disruption is reliably associated with various adverse mental health and wellbeing outcomes, including major depressive disorder and bipolar disorder. Lower relative amplitude might be linked to increased susceptibility to mood disorders. Funding: Lister Institute of Preventive Medicine.